Family foster care: perceptions of Portuguese child protection professionals - Negrão, Mariana (2022)
Family foster care (FFC) is the preferred out-of-home care measure for the protection of children and youth through Europe, in accordance with research findings of its superiority in meeting developmental needs of children and youth. Portugal, however, does not accompany the European trend in the implementation of FFC. Even after changes made to the law, prioritizing FFC, it represents only 2,7% of out-of-home placements (Instituto de Segurança Social, I.P. [ISS-IP], 2020).The main goal of this exploratory and descriptive study is to understand the perceptions of Portuguese child protection professionals concerning FFC. 101 participants, from different professional backgrounds and child protection contexts, filled out a questionnaire. Main findings show a heterogeneous degree of familiarity to FFC, and a generally positive although reserved attitude to it. Professionals seem to value its child-centred approach and ability to promote child development and healthy attachment relationships, due to the benefits of a family environment. Participants identified regulations and procedures related to selection, evaluation, training, and support to foster families both as obstacles and necessary conditions for placement success, indicating important arenas where change urges.